CURRENT PATH TO COMMUNITY BASED SUSTAINABLE TOURISM DEVELOPMENT OF KHANH HOA PROVINCE IN VIETNAM - Pham Bich Ngoc; Nguyen Hoang Tien; Tran Thi Thuy Trang (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The article analyzes the current situation of Khanh Hoa province (Vietnam) tourism in terms of sustainable development in the period 2010-2019. This is the result of the research project "Model of sustainable tourism development with community participation in Khanh Hoa province" from September 2019 to November 2020 by Pham Bich Ngoc. The study used PESTEL method and surveyed tourists to Khanh Hoa province with 726 samples. The research results show that Khanh Hoa province tourism develops very quickly but is not really sustainable. There are still many problems that need to be adjusted, especially when it is strongly affected by the external environment. Besides, the article also gives some policy implications to help Khanh Hoa province develop sustainable tourism in the future. I